2012
DOI: 10.4161/adip.21042
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of brown adipose tissue

Abstract: Brown adipose tissue (BAT), an important endocrine organ long known for thermogenesis and energy consumption, has received much attention in recent years for its potential to combat obesity. In general, BAT can enhance metabolism and improve overall health. Our recent work demonstrates the ability of embryonic BAT transplants to correct type 1 diabetes (T1D) without insulin, via mechanisms somewhat different from those involved in BAT-associated weight loss. BAT transplants seem to reverse T1D by decreasing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Brown adipocytes are the major constituents of brown adipose tissue (BAT), which is situated in the interscapular, cervical, mediastinal and retroperitoneal regions [3,4]. BAT plays a prominent role in thermogenesis and energy expenditure [5]. In 1976, Ricquier et al found a particular 32,000 Mr membranous protein in rat BAT mitochondria, which was upregulated upon cold exposure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Brown adipocytes are the major constituents of brown adipose tissue (BAT), which is situated in the interscapular, cervical, mediastinal and retroperitoneal regions [3,4]. BAT plays a prominent role in thermogenesis and energy expenditure [5]. In 1976, Ricquier et al found a particular 32,000 Mr membranous protein in rat BAT mitochondria, which was upregulated upon cold exposure [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, much effort has been made to identify human brown adipose-derived stem cells [35], or manipulate human pluripotent stem cells (embryonic stem cells) into brown-specific progenitor cells [36,37]. These classical brown adipocyte models have significantly contributed to the identification of the transcriptional regulatory pathways of brown adipocytes and possess great therapeutic potential for the treatment of obesity [38]. However, classical brown adipocyte cultures are not an attractive model for studying human adaptive thermogenesis due to the paucity of classical BAT in humans; even in infants, beige adipocytes seem to be more prevalent than classical brown fat [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been a plethora of research investigating ways to enhance the expression of thermogenes in WAT. The resulting beige tissue is hypothesized to combat obesity by reducing lipids stored within WAT and increasing energy expenditure [2], [3], [5], [21], [22]. These attempts to induce beige fat necessitate the development of sensitive and specific, translatable, imaging methodologies to accurately detect beige fat mass in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically active brown adipose tissue (BAT) plays a significant role in metabolism and energy regulation [1], [2], [3]. While white adipose tissue (WAT) is responsible for energy storage, BAT is responsible for dissipating energy through the action of the uncoupling protein-1 (UCP1).…”
Section: Introductionmentioning
confidence: 99%